How Managers Can Create Happy Working Environment - Denisa ABRUDAN; Iulia CONEA-SIMIUC (Revista de Management Comparat International)
Do you know that happy employees are one of the most significant factor when you think about productivity and satisfied customers? It is important to analyze if the benefit packages offered by today's companies are tailored to the needs of the employees. Historically, there has been a strong correlation between wealth and happiness, so are the benefit packages good enough in order to be a factor in attract and retain the outstanding employees that show commitment towards work? Can these benefits impulse the employees to achieve superior output at work? Will the employees be happier and relying on this state, to overcome their limits in everyday job tasks? A proposal in order to achieve this state of happiness among the employees would be to provide a tailored system of C&B that meet the employees' expectations, system, which also includes the well-being concept. According with a study realised by Social Market Foundation in 2015, happy employees are up to 20% more productive than unhappy employees. When it comes to sales people, happiness has an even greater impact, raising sales by 37%. But the benefits don't end there, also happy employees will have better decision-making abilities and greater innovation abilities, also will be a reduction in lost productivity and better customer service. The present paper work describes, within theoretical aspects and a practical case, the role of occupational welfare in having happy, committed employees and successful organizations.